Electrochemical Catalysts for Green Hydrogen Energy. Issue 7 (7th May 2021) - Hyung Kweon, Do; Jeon, In-Yup; Baek, Jong-Beom
Abstract : Developing clean and renewable energy resources has become one of the world's most important challenges, given the double burden of energy scarcity and environmental pollution. For sustainable energy conversion and storage, efficient electrocatalysts play a pivotal role in important energy‐related reactions, including oxygen reduction, oxygen evolution, and hydrogen evolution. To satisfy practical requirements, the catalysts need to demonstrate high performance, durability, and acceptable cost. These are primary considerations when designing and preparing various new electrocatalysts. Among the research programs being actively conducted around the world, some promising recent results suggest strong potential alternatives to current expensive noble metal‐based catalysts. This review summarizes recent technical advances in the preparation of efficient electrocatalysts. Abstract : This work summarizes recent advances in electrocatalysts for oxygen reduction, oxygen evolution, and hydrogen evolution reactions for energy conversion and storage systems. Electrocatalysts for each reaction is categorized based on working principle, structural design, performance comparison, and remaining challenges. This review suggests a future research direction for electrocatalysts to realize hydrogen economy.